Analisis Framing Berita Berjudul “Presiden Jakarta Selatan” di Majalah Tempo Edisi 22-28 April 2019 - Putra Perwira Guna Lubis; Leylia Khairani (CERED Indonesia, 2020)
The events of the Presidential Election in the United States in 2020 are similar to the political events of the 2019 Presidential Election in Indonesia, where Prabowo Subianto also claimed victory, accused of fraud, and also said he would sue the election results. If we look at the political events in 2019, the statement of Prabowo Subianto-Sandiaga Uno's victory claim as President and Vice President of the Republic of Indonesia for 2019-2024 on the same day after the election on April 17, 2019, has the potential to cause conflict. Moreover, coupled with the plan to create a “people power” movement which was interpreted as a way to win camp 02, the political situation in Indonesia was increasingly heated. So this research intends to see how the mass media, especially Tempo Magazine, which in 2019 framed issues related to Prabowo's victory claim. The object of this research is the news entitled